Influence of silicon nanocrystals on the performance of Yb3+/Er3+: Bi2O3-GeO2 pedestal waveguides for amplification at 1542 nm - Da Silva, Diego S.; Alayo, Marcos I.; Kassab, Luciana R. P. [UNESP]; De Assumpção, Thiago A. A.; Wetter, Niklaus U.; Jimenez-Villar, Ernesto [UNESP] (SPIE, the international society for optics and photonics, 2018)
This paper reports for, the first time, the influence of silicon nanocrystals on the photoluminescence and optical gain of Yb3+/Er3+ codoped Bi2O3-GeO2 waveguides for amplification at 1542 nm. Pedestal waveguides were fabricated by RF- sputtering followed by optical lithography and reactive ion etching. RF-sputtering followed by heat treatment produced silicon nanocrystals with average size of 8 nm and resulted in a photoluminescence enhancement of about 10 times for the 520 nm and 1530 nm emission bands. The resulting internal gain was 5.5 dB/cm at 1542 nm, which represents and enhancement of ∼50%, demonstrating potential for applications in integrated optics.
Keywords: Nanomaterials; Optical amplifiers; Photoluminescence; Waveguides